Psychological Determinants of Physical Activity and Development in Early Childhood Among Children With Developmental Delays: The Role of Parent Beliefs Regarding the Benefits of Physical Activity - Lakes, Kimberley D.; Neville, Ross D.; Abdullah, Maryam; Donnelly, Joseph (Frontiers in Sports and Active Living, 2020)
Among the various psychological determinants of physical activity (PA) in early childhood, relatively little attention has been paid to the role of parent beliefs in the benefits of PA for their child. Believing that PA is beneficial may impact parent behavior, resulting in more opportunities for PA in early childhood. This, in turn, may promote the development of motor skills and healthy body composition. This study examined the association between parental beliefs about PA and overweight in 147 children (32 ± 4 months old) with developmental delays, adjusting for socioeconomic, child- and parent-level covariates, including parent reports of their child’s motor development and weekly PA. Eight percent of parents with above average (mean +1SD) perceptions of the benefits of PA had children who were overweight or obese. The proportion was almost 4 times (proportion ratio, 3.99; 95% CI, 1.40 to 11.37) higher for parents with below average (mean – 1SD) perceptions. Ethnicity and mothers’ self-reported depressive symptoms were the only other tested covariates associated with the weight status of these children. Our study demonstrates the importance of considering parental or caregiver beliefs in the value of PA as another risk factor that may predict risk for overweight and obesity. Future studies should include parent beliefs in the benefits of PA as a potential psychological determinant of PA and associated health outcomes.